Ultrasound assessment of oxaliplatin‐induced neuropathy and correlations with neurophysiologic findings. Issue 1 (4th September 2012) - Briani, C.; Campagnolo, M.; Lucchetta, M.; Cacciavillani, M.; Dalla Torre, C.; Granata, G.; Bergamo, F.; Lonardi, S.; Zagonel, V.; Cavaletti, G.; Ermani, M.; Padua, L.
<x xml:space="preserve">Abstract</x> Background and purpose Chemotherapy‐induced peripheral neuropathy is a major adverse effect of oxaliplatin (OXL) treatment. Whereas neurophysiologic study is commonly used to assess the occurrence and severity of polyneuropathies, ultrasound (US) analysis of the peripheral nerves, an emerging technique in the study of peripheral nerve diseases, has never been used in chemotherapy‐induced peripheral neuropathy. Patients and methods Fifteen patients (four women; 11 men; mean age, 60.1 ± 10.6 years; median, 62; range, 37–75) with colorectal cancer treated with OXL‐based treatment have been clinically and neurophysiologically evaluated before and after OXL therapy. At the end of chemotherapy, all patients underwent also nerve US study at four limbs, and the findings correlated with clinical and neurophysiologic measures. Results Clinical and neurophysiological evaluation showed that 13 of 15 (86.7%) patients developed sensory axonal neuropathy, 10 of whom severe (two or more sensory nerve action potential amplitude absent and the other amplitudes decreased of ≥50%). Nerve US did not reveal decreased cross‐sectional area (CSA), a reported finding in axonal neuropathies. Instead increased CSA at entrapment sites (median nerve at wrist and ulnar nerve at elbow) was found in 09/15 (60%) of patients. Discussion Sensory axonal neuropathy is a very common complication of OXL therapy, affecting almost 90% of patients. US findings of enlargement of median and ulnar nerves, mostly at entrapment sites, in patients with no history or symptoms of neuropathies at recruitment, and no neurophysiologic evidence of entrapment, may be expression of increased, OXL‐induced, nerve susceptibility to mechanical damage. An ongoing prospective study will help clarify these findings.